Impact of Nutrition Education on Knowledge of Rural Women - Anuradha Ranjan Kumari , Basanti Kumari; Laxmikant (Indian Journal of Extension Education, 2015)
Nutrition Education is any combination of educational strategies, accompanied by environmental supports, designed to facilitate voluntary adoption of food choices and other food and nutrition related behaviors conducive to health and well being. Nutrition education is delivered through multiple venues and involves activities at the individual, community, and policy levels. A longitudinal study indicated the impact of nutrition education on rural women of Salempur block of Deoria district. Aspecial nutrition training programme revealed that nutrition education affected an increase in knowledge gain, the motivation of women improvement reflected in the selection of food, cooking practices with increase in nutritive value of food. The most significant improvement was observed in the fuel consumption pattern, balanced diet and conservation of nutrients. It was observed that rural women motivated and guided efficiently. It would definitely faster desirable change in them which ultimately results in bringing improvement in the nutritional status of community as a whole.